Conceptualisations of children's wellbeing at school: The contribution of recognition theory. (November 2016) - Thomas, Nigel; Graham, Anne; Powell, Mary Ann; Fitzgerald, Robyn
A large study in Australian schools aimed to elucidate understandings of 'wellbeing' and of factors in school life that contribute to it. Students and teachers understood wellbeing primarily, and holistically, in terms of interpersonal relationships, in contrast to policy documents which mainly focused on 'problem areas' such as mental health. The study also drew on recognition theory as developed by the social philosopher Axel Honneth. Results indicate that recognition theory may be useful in understanding wellbeing in schools, and that empirical research in schools may give rise to further questions regarding theory.